The politics of space architecture, painting, and theater in postmodern Germany - Nash, Douglas 1962- (New York P. Lang, 1996)
"This multigeneric study applies a spatial terminology to three well-known German-speaking artists: architect Hans Hollein, painter Anselm Kiefer and dramatist Heiner Muller. It explores their efforts to place themselves, sometimes critically, within the confusing and commodified landscape of postmodern culture. Along the way, the study indicates the difficulty for progressive cultural activity today." -- Provided by publisher
Chapter 1 Introduction: anti-foundational landscapes and postmodern space -- Chapter 2 Simulated space: Hans Hollein and the contemporary museum -- Chapter 3 Figured space: Anselm Kiefer and the "Bildersreit" -- Chapter 4 Commodified space: Heiner Muller and the postmodern image -- Chapter five Summary
Includes bibliographical references (pages 211-232).
FA-2663g donated by German Cultural Center Library.
Keywords: Arts, German -- 20th century; Postmodernism -- Germany; Arts, Modern -- 20th century -- Germany